Enlightenment and religion in German and Austrian literature - Robertson, Ritchie (Selected essays (Modern Humanities Research Association) ;, 2017)
Religion and enlightenment, the twin themes of this volume, always exist in tension. The tensions, affinities, and conflicts between the two, as they play out in German literature from Goethe, Schiller and Kleist down to Kafka and Thomas Mann, are explored in this volume, with one section examining their interplay in the neglected Austrian Enlightenment. Thanks to the historical and textual criticism of the Bible, the 'sea of faith' began its withdrawal sooner in Germany than in England, and this collection traces its retreat, looking especially at Nietzsche's militant opposition to Christianity and at the expression in some modernist writing of a distinctly post-Christian and even post-human outlook.